2022
DOI: 10.1108/ecam-02-2022-0108
|View full text |Cite
|
Sign up to set email alerts
|

Dispute root causes and prevention in Iranian public-private partnership projects: a causal-predictive model

Abstract: PurposePublic–private partnerships (PPPs) are notoriously prone to disputes among stakeholders, some of which may unduly jeopardize contract performance. Contract disputes arising in Iran are often due to inefficiency of PPP concession agreements and practice. This study presents a causal-predictive model of the root causes and preventive measures for inter-organization disputes to enhance the likelihood of achieving desirable performance in PPP projects.Design/methodology/approachA theoretical “causal-predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…This study's findings have identified the final 21 barriers based on questionnaires, followed by prioritized barriers using mean scores, classified barriers consisted of 5 clusters, ranked strategies to alleviate the barriers and determined execution period. Meanwhile, previous studies have revealed different findings and have not determined the execution period for implementing the barrier-alleviation strategies, such as Amiri et al (2022), Cao et al (2022), Owusu-Manu et al (2022, Adu Gyamfi et al (2022), Ghorbany et al (2022), Mirzaee et al (2022), ECAM 31,8 Wang et al (2022). The possible reason for the different barriers identified is that this study focuses on the war-torn country of Palestine.…”
Section: Barrier Group 5: Deficiency Of Law Constancymentioning
confidence: 87%
See 2 more Smart Citations
“…This study's findings have identified the final 21 barriers based on questionnaires, followed by prioritized barriers using mean scores, classified barriers consisted of 5 clusters, ranked strategies to alleviate the barriers and determined execution period. Meanwhile, previous studies have revealed different findings and have not determined the execution period for implementing the barrier-alleviation strategies, such as Amiri et al (2022), Cao et al (2022), Owusu-Manu et al (2022, Adu Gyamfi et al (2022), Ghorbany et al (2022), Mirzaee et al (2022), ECAM 31,8 Wang et al (2022). The possible reason for the different barriers identified is that this study focuses on the war-torn country of Palestine.…”
Section: Barrier Group 5: Deficiency Of Law Constancymentioning
confidence: 87%
“…financial innovations, viability research, macro-atmosphere effect, proper financing choice, risk detection, transfer, sharing and allocation, financial setup and conformity with the regulatory and legal agenda. In other PPP construction projects in Iran, academicians Mirzaee et al. (2022) disclosed three most vital barriers: failure to enable a well-timed approval process, inappropriate payment system and risk misallocation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation